Terapi untuk Mengatasi Body Image Dissatisfaction pada Remaja Oveerweight - Glory Grifith. B Saragih; Iyus Yosep; Efri Widianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the therapies that can be used to reduce body image dissatisfaction in overweight adolescents. The research method used is scoping review through electronic databases Science Direct, Google Scholar, EBSCO, and Pubmed. The search results from several databases found eight articles that match the research criteria. Some of these articles show that Cognitive Behavior Therapy (CBT), Acceptance Commitment Therapy (ACT), Media Exposure Video Artificial Beauty, Long-Term Multidisciplinary Lifestyle Therapy, Gratitude Journals, and Self Affirmation affect reducing the level of body image dissatisfaction in adolescents who experience overweight. In conclusion, several effective therapies can be used to reduce mental health problems experienced by adolescents who are overweight. The target of this therapy is to reduce body image dissatisfaction in fat people so that it does not cause other mental health disorders that can threaten the person's life. Some of these therapies can help overcome dissatisfaction with the body due to being overweight. Keywords: Body Image Dissatisfaction, Overweight, Therapy